2022
DOI: 10.1021/acs.est.2c05001
|View full text |Cite
|
Sign up to set email alerts
|

Sulfamethoxazole Enhances Specific Enzymatic Activities under Aerobic Heterotrophic Conditions: A Metaproteomic Approach

Abstract: The growing concern about antibiotic-resistant microorganisms has focused on the sludge from wastewater treatment plants (WWTPs) as a potential hotspot for their development and spread. To this end, it seems relevant to analyze the changes on the microbiota as a consequence of the antibiotics that wastewater may contain. This study aims at determining whether the presence of sulfamethoxazole (SMX), even in relatively low concentrations, modifies the microbial activities and the enzymatic expression of an activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The MHNAD bacteria took a short period for adaptation to each elevated ATS dose. It was reported that the microbial activity could be recovered if the antibiotic concentration was below the tolerance threshold . The mean ORE and TNRE reached 95.2 and 100%, respectively, at [ATS] 0 = 36 mg·L –1 (day 80).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MHNAD bacteria took a short period for adaptation to each elevated ATS dose. It was reported that the microbial activity could be recovered if the antibiotic concentration was below the tolerance threshold . The mean ORE and TNRE reached 95.2 and 100%, respectively, at [ATS] 0 = 36 mg·L –1 (day 80).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the microbial activity could be recovered if the antibiotic concentration was below the tolerance threshold. 28 The mean ORE and TNRE reached 95.2 and 100%, respectively, at [ATS] 0 = 36 mg•L −1 (day 80). Meanwhile, the EPS content increased to 81.6 ± 1.1 mg•g-MLVSS −1 (Figure S1), indicating that the MHNAD bacteria produced more EPSs to enhance resistance to ATS.…”
Section: Long-term Organic and Nitrogen Removals By The Mhnad Processmentioning
confidence: 94%
“…The SMX removal performance of the Janus ERM was investigated via single-pass filtration (i.e., mode I in Figure b). The antibiotic SMX was applied as the model MP, as it has been extensively used and detected in numerous water sources, e.g., surface water, municipal sewage, and hospital effluents. The Janus ERM enabled 81.8% removal of SMX in a single-pass electrofiltration with the presence of a BSA macromolecule in the feed solution (Figure c). The SMX removal efficacy of other electrofiltration and nonelectrified filtration modes was determined for comparison.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Antibiotics are an emerging micropollutant and a cause of significant concern. , Sulfamethoxazole (SMX), a common antibiotic, is a low-adsorption polar sulfonamide and is often found in wastewater, surface water, and groundwater. , Given that only moderate antibiotic degradation can be achieved in sewage pipes, wastewater treatment plant (WWTP) effluents have high concentrations of SMX (ng/L-μg/L). Furthermore, most SMX excreted into wastewater is primarily in the form of human transformation products N -acetyl-SMX (43–55%) and N -SMX glucuronide (10–13%) . Of note, N -acetyl-SMX and N-SMX glucuronide easily cleave into SMX molecules during the treatment process, thereby increasing the SMX concentration in WWTP effluents …”
Section: Introductionmentioning
confidence: 99%